When ESKD complicates the management of pain. Issue 3 (4th May 2020) - Jhamb, Manisha; Tucker, Laura; Liebschutz, Jane
Abstract: Pain is one of the most common symptoms reported by patients with end‐stage kidney disease (ESKD) and negatively impacts their health‐related quality of life (HRQOL), dialysis adherence, healthcare utilization, and mortality. There are a number of patient‐related and health system‐related barriers that make it very challenging to treat pain in these patients. Moreover, the limited availability of efficacious and safe nonopiate analgesic options has led to over‐use of opioids in this population. We propose a framework for pain assessment and tailored treatment using nonpharmacological and pharmacological approaches to optimize pain management and opioid use. Additionally, we recommend system‐level changes to improve care coordination and pain management in ESKD patients.